ARTIFICIAL INTELLIGENCE IN MANAGEMENT: AUTOMATION OF PROCESSES AND DECISION-MAKING - Kalach, Hanna; Shpak, Oleksandr; Kruhlyanko, Andriy (Social Development: Economic and Legal Issues, 2025)
This article proposes promising methods for applying artificial intelligence in management and decision-making processes. In today's management environment, characterized by dynamic digitalization, the issue of effective use of artificial intelligence tools for process automation and management decision-making is becoming increasingly relevant. The purpose of the study is to analyze the potential of artificial intelligence as a factor in improving the effectiveness of strategic management in the context of digital transformation and cyber threats. The article analyzes modern concepts of artificial intelligence implementation in management, in particular the use of machine learning algorithms for data analysis, communication personalization, and customer interaction management through chatbots and virtual assistants. The possibilities of using artificial intelligence to improve the accuracy of decision-making, as well as to ensure transparency and efficiency of communications, are considered. The impact of artificial intelligence tools on the transformation of the media space, the development of digital analytics, visualization, gamification, and crowdsourcing is determined. Particular attention is paid to challenges related to confidentiality, ethical use of data, information security, and trust in digital tools. Recommendations are made for optimizing management strategies, taking into account current digital trends. Artificial intelligence is identified as an effective tool for improving management efficiency, providing a personalized approach, rapid response, and data-driven decision-making. At the same time, the introduction of artificial intelligence is accompanied by the need for new skills, ethical standards, and cybersecurity guarantees. A promising area for further research is the development of mechanisms for assessing the ethical impact of artificial intelligence on management processes.